2006
DOI: 10.1200/jco.2006.06.2497
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Cardiovascular Disease During Androgen Deprivation Therapy for Prostate Cancer

Abstract: GnRH agonist treatment for men with locoregional prostate cancer may be associated with an increased risk of incident diabetes and cardiovascular disease. The benefits of GnRH agonist treatment should be weighed against these potential risks. Additional research is needed to identify populations of men at highest risk of treatment-related complications and to develop strategies to prevent treatment-related diabetes and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
1,002
2
31

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,317 publications
(1,070 citation statements)
references
References 37 publications
35
1,002
2
31
Order By: Relevance
“…Epidemiological studies have implicated that ADT may be partly responsible for the increased number of CVD events, which is observed shortly after treatment initiation and most notably in patients with preexisting atherosclerotic CVD 4, 9. These observations are strongest for GnRH agonists, the most common form of ADT, whereas data on orchiectomy are less consistent and little information still exists pertaining to the newer GnRH antagonists 9, 26. In 2010, the combined observations led the U.S. Food and Drug Administration to put a warning label on GnRH agonists regarding the suspected increased risk of CVD (http://www.fda.gov/drugs/drugsafety/ucm229986.htm).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have implicated that ADT may be partly responsible for the increased number of CVD events, which is observed shortly after treatment initiation and most notably in patients with preexisting atherosclerotic CVD 4, 9. These observations are strongest for GnRH agonists, the most common form of ADT, whereas data on orchiectomy are less consistent and little information still exists pertaining to the newer GnRH antagonists 9, 26. In 2010, the combined observations led the U.S. Food and Drug Administration to put a warning label on GnRH agonists regarding the suspected increased risk of CVD (http://www.fda.gov/drugs/drugsafety/ucm229986.htm).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also confirmed this connection between ADT, insulin resistance and hyperglycemia. 13,23,24 Although metabolic changes are sometimes neglected in the early phase, they can start as early as 3 months after treatment. Fasting insulin is a more sensitive index compared to fasting blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Some of the complications have negative effects on quality of life assessments, while others may induce serious problems including myocardial infarction and sudden cardiac death. 13 A longterm study revealed that 53% of the deaths were not attributable to prostate cancer. Of these cases, cardiovascular problems are the predominant causes.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Furthermore, recent data have linked ADT to an increased risk of cardiovascular morbidity and mortality, including new onset diabetes, coronary artery disease and sudden cardiac death. [9][10][11][12] When ADT fails, patients with hormone-refractory PC have fewer treatment options and a poorer prognosis as the mainstay of therapy is cytotoxic chemotherapy that confers a mere 2-month survival advantage. 13 In recent years, increased attention has focused on exercise as a supportive adjunct therapy following a cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%